Implementation of Random Shuffle Algorithm to Randomize Questions in Anti-Corruption Prevention Game - Askar; Pasnur; Asrul; Amran Amiruddin; Muhammad Resha; Andri Wijaya T (Yayasan Cita Cendekiawan Al Khwarizmi, 2023)
Socializing anti-corruption education in Indonesia is crucial to fostering public aversion towards corruption. Games are a highly effective medium for disseminating anti-corruption prevention during school years. This research aims to implement anti-corruption education within a game using the shuffle random algorithm to ensure the successful randomization of anti-corruption questions. This data was obtained through a literature review. The method used in this study is the Multimedia Development Life Cycle (MDLC). The results of this research indicate that the testing yielded a 100% accuracy rate for the shuffle random algorithm in randomizing the questions. The accuracy rate demonstrates that the shuffle random algorithm can effectively randomize the questions and is easy to implement.